The marine ichthyofauna of Lebanon: an annotated checklist, history, biogeography, and conservation status - Bariche, Michel; Fricke, Ronald (Zootaxa, 2020)
This is an annotated checklist of the marine fish species of Lebanon (Levant coast, eastern Mediterranean). It comprises a total of 367 fish species distributed in 159 families and 27 orders, out of which 70 species are non-indigenous and 28 are recorded for the first time from Lebanon. The checklist includes all names and citations of species found in the literature, as well as references to specimens available in museum collections. It also includes an updated zoogeographic distribution and conservation status for each species. Threats were estimated based on surveys and observations made over the last two decades; broadly categorized conservation actions were also suggested.